Whole‐heart coronary MR angiography using a 3D cones phyllotaxis trajectory. Issue 2 (29th October 2018) - Malavé, Mario O.; Baron, Corey A.; Addy, Nii Okai; Cheng, Joseph Y.; Yang, Phillip C.; Hu, Bob S.; Nishimura, Dwight G.
Abstract : Purpose: To develop a 3D cones steady‐state free precession sequence with improved robustness to respiratory motion while mitigating eddy current artifacts for free‐breathing whole‐heart coronary magnetic resonance angiography. Method: The proposed sequence collects cone interleaves using a phyllotaxis pattern, which allows for more distributed k‐space sampling for each heartbeat compared to a typical sequential collection pattern. A Fibonacci number of segments is chosen to minimize eddy current effects with the trade‐off of an increased number of acquisition heartbeats. For verification, phyllotaxis‐cones is compared to sequential‐cones through simulations, phantom studies, and in vivo coronary scans with 8 subjects using 2D image‐based navigators for retrospective motion correction. Results: Simulated point spread functions and moving phantom results show less coherent motion artifacts for phyllotaxis‐cones compared to sequential‐cones. Assessment of the right and left coronary arteries using reader scores and the image edge profile acutance vessel sharpness metric indicate superior image quality and sharpness for phyllotaxis‐cones. Conclusion: Phyllotaxis 3D cones results in improved qualitative image scores and coronary vessel sharpness for free‐breathing whole‐heart coronary magnetic resonance angiography compared to standard sequential ordering when using a steady‐state free precession sequence.